PERAN WHO UNTUK MENGENTASKAN PENYAKIT MALARIA DI TIMOR-LESTE TAHUN 2016-2018 - Reis Saldanha, Deadora Isabel Dos; Kumala Dewi, Putu Ratih; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This research aims to analyze the role of the World Health Organizations (WHO) eliminating malaria in Timor Leste, 2016-2018. WHO carries out its role through the implementation of the Global Technical Strategy for Malaria 2016-2030. This program’s objective is to eliminate malaria according to the 3rd point of the Sustainable Development Goals (SDGs), namely Good Health and Well-Being. The government of Timor Leste had made various attempts to eliminate malaria, but the target wasn’t achieved. WHO is helping Timor Leste to achieve SDG targets in the elimination of malaria through its role. This study obtained the results that WHO has performed various roles to eliminate malaria in Timor-Leste. These roles are divided into prevention and control; diagnosis and treatment; as well as elimination and evaluation. WHO provides support in the form of medical guidelines and recommendations; promotions and campaigns; training for medical personnel; and direct intervention to malaria endemic areas.   Keywords: World Health Organizations (WHO), Global Fund for AIDS, Malaria, Timor Leste